2015
DOI: 10.3138/jcfs.46.4.467
|View full text |Cite
|
Sign up to set email alerts
|

Being a Traditional Dad or Being More Like a Mum? Clashing Models of Fatherhood According to Swedish and Polish Fathers

Abstract: The purpose of this article is to document how Swedish and Polish fathers understand their parental roles in the times of changing gender relations. An important question is how they deal with two conflicting models of fatherhood—the traditional model based on breadwinning and the new model of involved fatherhood. I argue here that fatherhood is a highly contextual phenomenon and the way men engage in parental roles is strictly connected with the social expectations and people’s assumptions about parenting and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…On the other hand, differences between parents in motivators for playing might be attributed to parents' perceptions about what is expected from them based on traditional gender roles [ 51 ]. Research suggests that gender roles are critical for defining the implicit objectives of parent-child interactions [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, differences between parents in motivators for playing might be attributed to parents' perceptions about what is expected from them based on traditional gender roles [ 51 ]. Research suggests that gender roles are critical for defining the implicit objectives of parent-child interactions [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…You don’t know how to deal with your own feelings, you don’t know how to deal with what your role should be in a family because there is no clear role for a man as a father.The rich descriptions of the participants experiences revealed the conflicts fathers face arising from the differing expectations in their role as a man and as a father. This uncertainty surrounding the role of a father may be due to the conflicting models of “new” and “traditional” fatherhood that men navigate (Suwada 2015). This study found that often Australian fathers try to contest “traditional” fatherhood by being more involved.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, an Australian study revealed that traditional fatherhood practices were often promoted by mothers, despite some fathers shifting to more egalitarian views (Buchler, Perales, and Baxter 2017; Doucet and Lee 2014). This push towards gendered parenting roles may result from institutional ideologies supporting “traditional” divisions of labor (Doucet and Lee 2014; Suwada 2015). Participants in Machin’s (2015) study expressed that society paid lip service to involved fatherhood with no genuine investment into implementing support systems or policies that allow fathers to be equally involved in raising children.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bununla birlikte, tıpkı geleneksel babalık rolünde olduğu gibi, söz konusu yeni babalık rolü doğrultusunda erkeğin üstlendiği sorumluluk ve yerine getirilmesi gereken görevler hem içinde bulunulan alt-üst kültürel yapı hem de bireyin toplumsal konumuna bağlı olarak farklılık gösterebilmekte (Daly, 1993;Lipasova, 2016;Marks & Palkovitz, 2004;Suwada & Plantin, 2011;Suwada, 2015;Wall vd., 2007;Walker & McLanahan, 1999), bu durum ise farklı babalık modellerinin ortaya çıkışını beraberinde getirmektedir. Babalık modelleri, bireyin ilgililik düzeyi ve üstlendiği babalık stilindeki farklılaşmanın açıklamasıdır (Marks & Palkovitz, 2004).…”
Section: Erkeklikler Hegemonik Erkeklik Ve Babalık Rolüunclassified